2003
DOI: 10.1183/09031936.03.00023303
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal pro-brain natriuretic peptide in patients with acute pulmonary embolism

Abstract: Plasma brain natriuretic peptide (BNP), released from myocytes of ventricles upon stretch, has been reported to differentiate pulmonary from cardiac dyspnoea. Limited data have shown elevated plasma BNP levels in acute pulmonary embolism (APE), frequently accompanied by dyspnoea and right ventricular (RV) dysfunction. The aim of this study was to assess plasma N-terminal proBNP (NTproBNP) in APE, and to establish whether it reflects the severity of RV overload and if it can be used to predict adverse clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(102 citation statements)
references
References 17 publications
3
86
2
11
Order By: Relevance
“…In addition, elevation of BNP has prognostic importance in pulmonary embolism; in one study (33), a BNP level of less than 21.7 pg/mmol excluded fatal pulmonary embolism with 99% accuracy, while a second study (34) demonstrated that a BNP level of less than 50 pg/mmol excluded an adverse outcome from acute pulmonary embolism with 95% accuracy. Similar findings were made with NT-proBNP levels in patients with acute pulmonary embolism (35). Therefore, being released by RV dysfunction in the absence of LV dysfunction, BNP elevations do not always suggest the presence of LV failure.…”
Section: Bnp Versus Nt-probnpsupporting
confidence: 73%
“…In addition, elevation of BNP has prognostic importance in pulmonary embolism; in one study (33), a BNP level of less than 21.7 pg/mmol excluded fatal pulmonary embolism with 99% accuracy, while a second study (34) demonstrated that a BNP level of less than 50 pg/mmol excluded an adverse outcome from acute pulmonary embolism with 95% accuracy. Similar findings were made with NT-proBNP levels in patients with acute pulmonary embolism (35). Therefore, being released by RV dysfunction in the absence of LV dysfunction, BNP elevations do not always suggest the presence of LV failure.…”
Section: Bnp Versus Nt-probnpsupporting
confidence: 73%
“…The study of Vuilleumier et al shows that NT-proBNP is the biomarker with the strongest predictive value in the risk stratification of patients with acute PE [16]. In other studies, the cut-off levels for NT-proBNP for the prediction of adverse events vary between 300 and 1,000 pg/ml [12][13][14][15][16]. This variation in cut-off levels is probably the result of factors as differences in assays, outcome definition, duration of clinical follow-up, inclusion criteria, and type of institution (primary versus secondary or tertiary care [16].…”
Section: Discussionmentioning
confidence: 99%
“…The inactive pro-hormone (pro-BNP) is split into the active hormone BNP and the inactive N-terminal fragment (NT-proBNP) [11]. Low (NT-pro)BNP concentrations are associated with an uncomplicated course in patients with acute PE and are therefore useful to identify low risk patients [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 4 studies have shown that low levels of natriuretic peptides on admission predict a benign clinical course. [1][2][3][4] The negative predictive value for in-hospital mortality ranged from 99% 3 to 100%. 1,2,4 Dr Krüger et al describe several PE patients with syncope who had normal pro-brain natriuretic peptide (BNP) levels but elevated troponin T levels on admission, suggesting that BNP mRNA synthesis, prohormone synthesis, and prohormone secretion into the circulation may take several hours after the onset of myocardial stretch.…”
Section: Responsementioning
confidence: 99%